Coronavirus Pandemic as an Opportunity to Increase Responsibility, Sacrifice, Altruism: An Experience of a Medical Intern - Vahid Tajari; Akram Sanagoo; Leila Jouybari (مجله ایرانی آموزش در علوم پزشکی, 2021)
letter To Editor